Active and Passive Islanding Detection for Photovoltaic System Integration - Yi Lung, Then; John Clairedora, Jezreel; Hadi Nabipour, Afrouzi (Semarak Ilmu Publishing, 2025)
In the context of photovoltaic (PV) system integration with the power grid, ensuring prompt and reliable islanding detection holds paramount importance for safety and operational stability. This study employs both active and passive islanding detection methods, assessing their efficacy through simulation and analysis. The active approach involves injecting a controlled test signal to manipulate PV systems, while the passive method monitors grid frequency deviations during islanding. Results indicate that both methods successfully and swiftly detect islanding events, with active detection identifying them within 0.5 seconds and passive detection within approximately 1 second. The study underscores the significance of these techniques for maintaining safe and stable PV-grid integration and conforms to IEEE 1547 standards through droop control strategies, all validated within a MATLAB/Simulink-based PV system simulation.